Exploring Common Therapeutic Targets for Neurodegenerative Disorders Using Transcriptome Study - Dharshini, S. Akila Parvathy; Jemimah, Sherlyn; Taguchi, Y. H.; Gromiha, M. Michael (Frontiers in Genetics, 2021)
Alzheimer’s (AD) and Parkinson’s (PD) diseases are well-known neuronal degenerative disorders that share common pathological events. The approved medications alleviate symptoms but do not address the root cause of the diseases. Energy dysfunction in the neuronal population leads to various pathological events and ultimately resulted in neuronal death. Identifying common therapeutic targets for these disorders may help in the drug discovery process. Brodmann area-9 (BA9) region is affected in both the disease conditions and plays an essential role in cognitive, motor, and memory-related functions. Analyzing transcriptome data of BA9 provides deep insights related to common pathological pathways involved in AD and PD. In this work, we map the preprocessed BA9 fastq files generated by RNA-seq for disease and control samples with reference hg38 genomic assembly and identified common variants and differentially expressed genes (DEG). These variants are predominantly located in the 3’UTR (nonpromoter) region, affecting the conserved transcription factor (TF) binding motifs involved in the methylation and acetylation process. We have constructed BA9-specific functional interaction networks, which show the relationship between TFs and DEGs. Based on expression signature analysis, we propose that MAPK1, VEGFR1/FLT1, and FGFR1 are promising drug targets to restore Blood-Brain-Barrier functionality by reducing neuroinflammation and may save neurons from the energy crisis.